Autopager: exploiting change blindness for gaze-assisted reading - Wilson, Andy; Williams, Shane (Proceedings of the 2018 ACM Symposium on Eye Tracking Research & Applications (ETRA '18), 2018)
A novel gaze-assisted reading technique uses the fact that in linear reading, the looking behavior of the reader is readily predicted. We introduce the AutoPager "page turning" technique, where the next bit of unread text is rendered in the periphery, ready to be read. This approach enables continuous gaze-assisted reading without requiring manual input to scroll: the reader merely saccades to the top of the page to read on. We demonstrate that when the new text is introduced with a gradual cross-fade effect, users are often unaware of the change: the user's impression is of reading the same page over and over again, yet the content changes. We present a user evaluation that compares AutoPager to previous gaze-assisted scrolling techniques. AutoPager may offer some advantages over previous gaze-assisted reading techniques, and is a rare example of exploiting "change blindness" in user interfaces.